The Effectiveness of Computer-Based Games as A Learning Media on The IUPAC Name of Inorganic Compounds - Rusly Hidayah; Nuril Lailiyah Iswahyuni; Rista Ajeng Mitasari (J-PEK (Jurnal Pembelajaran Kimia), 2021)
Learning media made must meet the eligibility criteria, one of which is effectiveness. The research was aimed to examine the effectiveness of computer-based games as a learning media on the nomenclature of an inorganic compound topic. This research used Plomp design research, which consists of three phases: preliminary phase, design prototype phase, and assessment phase. This research trial was 28 students in X grade at Senior High School 1 Puri Mojokerto used one group pretest and posttest design. The game's effectiveness s is based on the n-gain score from the pretest and posttest results, which data is normalized by Kolmogorov-Smirnov non-parametric test. The results of the n-gain calculation are 71.4% of students in one class have a moderate n-gain category, 21.42 % of students have a high n-gain category, and 7.18% of students have low n-gain criteria. Thus, it can be concluded that computer-based games are effective learning media.REFERENCESArsyad, A. (2013). Media Pembelajaran. Jakarta: PT RajaGrafindo Persada.Brensell, & Hansen, C. (2010). Designing an Educational Game: Design Principles From a Holistic Perspective. International Journal of Learning, 17 (10), 279-920.Chandel, P. D. (2015). Digital Game-Based Learning in Computer Science Education. CPUH Res. J 1(2), 33-37.Dananjaya, U. (2017). Media Pembelajaran Aktif cetakan ke-4. Bandung: Nuansa Cendekia.Hake, R. R. (1998). Interactive Engagement Versus Traditional Methods: A Six Thousand Student Survey of Mechanics Test Data for Introductory Physics Courses. 66.Lutfi, A., & Hidayah, R. (2017). Activating Student to Learn Chemistry using Chemmy Card 6-1 Game as an Instructional Medium in IUPAC Nomenclature of Inorganic CompoundManero, B. e. (2015). Can Educational Video Games Increase High School Students' Interest In Theatre? Computers and Education Journal, 182-191.Maulidina, M. A., Susilaningsih, & Abidin, Z. (2018). Pengembangan Game Based Learning Berbasis Pendekatan Saintifik Pada Siswa Kelas IV Sekolah Dasar. Jurnal Teknologi Pendidikan, Fakultas Ilmu Pendidikan, Universitas Negeri Malang, 113-Nunes, Lima, Miranda, Junior, Alexandre, Carlos, et al. (2017). Nomenclature Bets: An Innovative Computer-Based Game To Aid Students in the Study of Nomenclature of Organic Compounds. Journal of Chemical Education (95), 899-902.Permendikbud. (2014). Peraturan Pemerintah No. 32 Tahun 2013 tentang Standar Kompetensi Lulusan dan Standar Isi. Jakarta: Permendikbud.Plomp, T. (2013). Educational Design Research: An Introduction. Enschede: SLO Netherland Institute for Curriculum Development.Riduwan. (2016). Skala Pengukuran Variabel-Variabel Penelitian. Bandung: Alfabeta.Sadiman. (2014). Media Pendidikan. Jakarta: PT Raja Grafindo Persada.Sardiman. (2001). Interaksi dan Motivasi Belajar Mengajar. Jakarta: PT Raja Grafindo Persada.Slameto. (2010). Belajar dan Faktor-Faktor Yang Mempengaruhinya. . Jakarta: Rineka cipta.Slavin, R. E. (2011). Psikologi Pendidikan : Teori dan Praktek Edisi Sembilan. Jakarta: PT Indeks.Sugiyono. (2017). Metode Penelitian Pendidikan Pendekatan Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.Supendi, Pepen, & Nurhidayat. (2007). Fun Game. Jakarta: Penerba Swadaya.